Amyloid-β Aggregation Inhibitory and Neuroprotective Effects of Xanthohumol and its Derivatives for Alzheimer’s Diseases - Wang, Xueli; Ho, See-Lok; Poon, Chung-Yan; Yan, Ting; Li, Hung-Wing; Wong, Man S. (Current Alzheimer Research, 2019)
Background: Xanthohumol has been reported to have cytoprotection through activation of Nrf2−ARE signaling pathway and; it has capability of scavenging free radicals, suggesting its potential for the prevention of neurodegeneration. However, the bio-incompatibility and blood-brain barrier impermeability of xanthohumol hindered its in vivo efficacy potential for treating Alzheimer’s disease (AD). Objective: We designed and prepared a series of xanthohumol derivatives to enhance the desirable physical, biological and pharmacological properties in particular the blood-brain barrier permeability for intervention of AD. Methods: We designed and synthesized a novel series of 9 xanthohumol derivatives. Their inhibitory effect on amyloid-β (1-42), Aβ1-42, oligomerization and fibrillation as well as neuroprotection against amyloid-β induced toxicities, were explored. Results: Among the 9 xanthohumol derivatives, some of them exhibited a moderate to high inhibitory effect on Aβ1-42 oligomerization and fibrillation. They were biocompatible and neuroprotective to the SH-SY5Y cells by reducing the ROS generation and calcium uploading that were induced by the amyloid- β. Importantly, two of the derivatives were found to be blood-brain barrier permeable showing promising potential for AD treatment. Conclusion: Two derivatives have been identified to be biocompatible, non-toxic, neuroprotective against Aβ-induced toxicities and blood-brain barrier permeable highlighting their promising potential as AD drug candidates for future clinical use.
Keywords: Derivatives of xanthohumol